The Potential Prebiotic Effects of Yacon (Smallanthus sonchifolius) in Colorectal Cancer - Verediano, Thaísa A.; Viana, Mirelle L.; das G.V. Tostes, Maria; Costa, Neuza M.B. (Current Nutrition & Food Science, 2021)
Background: Colorectal cancer is caused by genetic predisposition and lifestyle risk factors and is associated with altered homeostasis of the intestinal microbiota. Evidence suggests that chronic infection and inflammation contribute to carcinogenic mutagenesis and promote cancer initiation and progression. Food components with prebiotic properties, such as fructooligosaccharides (FOS), promote intestinal integrity and health benefits. Yacon (Smallanthus sonchifolius) is an abundant source of FOS, which are fermented by beneficial bacteria, improving the intestinal environment affected by colorectal cancer. Objective: In the current review, the aim was to discuss colorectal cancer and its inflammatory process of development. Also, some general aspects concerning yacon roots and its prebiotic properties are described. Finely, the beneficial effects of yacon to reduce intestinal parameters altered due to colorectal cancer are summarized. Conclusion: It was verified that yacon might improve immunological parameters, intestinal barrier, intestinal microbiota, and inflammation in induced colorectal cancer in animals, especially. Researches with humans must be further investigated to prove these positive effects.
Keywords: microbiota